Comparison of Routing Metrics for Static Multi-Hop Wireless Networks - Zill, Brian; Draves, Rich; Padhye, Jitu (SIGCOMM, 2004)
Routing protocols for wireless ad hoc networks have traditionally focused on ﬁnding paths with minimum hop count. However, such paths can include slow or lossy links, leading to poor throughput. A routing algorithm can select better paths by explicitly taking the quality of the wireless links into account. In this paper, we conduct a detailed, empirical evaluation of the performance of three link-quality metrics— ETX, per-hop RTT, and per-hop packet pair—and compare them against minimum hop count. We study these metrics using a DSR-based routing protocol running in a wireless testbed. We ﬁnd that the ETX metric has the best performance when all nodes are stationary. We also ﬁnd that the per-hop RTT and per-hop packet-pair metrics perform poorly due to self-interference. Interestingly, the hop-count metric outperforms all of the link-quality metrics in a scenario where the sender is mobile.